Understanding the Impact of Hydrogen Activation by SrCe0.8Zr0.2O3−δ Perovskite Membrane Material on Direct Non-Oxidative Methane Conversion - Cheng, Sichao; Oh, Su Cheun; Sakbodin, Mann; Qiu, Limei; Diao, Yuxia; Liu, Dongxia (Frontiers in Chemistry, 2022)
Direct non-oxidative methane coupling (DNMC) converts methane (CH4) in one-step to olefin and aromatic hydrocarbons and hydrogen (H2) co-product. Membrane reactors comprised of methane activation catalysts and H2-permeable membranes can enhance methane conversion by in-situ H2 removal via Le Chatelier’s principle. Rigorous description of H2 kinetic effects on both membrane and catalyst materials in the membrane reactor, however, has been rarely studied. In this work, we report the impact of hydrogen activation by hydrogen-permeable SrCe0.8Zr0.2O3−δ (SCZO) perovskite oxide material on DNMC over an iron/silica catalyst. The SCZO oxide has mixed ionic and electronic conductivity and is capable of H2 activation into protons and electrons for H2 permeation. In the fixed-bed reactor packed with a mixture of SCZO oxide and iron/silica catalyst, stable and high methane conversion and low coke selectivity in DNMC was achieved by co-feeding of H2 in methane stream. The characterizations show that SCZO activates H2 to favor “soft coke” formation on the catalyst. The SCZO could absorb H2 in-situ to lower its local concentration to mitigate the reverse reaction of DNMC in the tested conditions. The co-existence of H2 co-feed, SCZO oxide and DNMC catalyst in the present study mimics the conditions of DNMC in the H2-permeable SCZO membrane reactor. The findings in this work offer the mechanistic understanding of and guidance for the design of H2-permeable membrane reactors for DNMC and other alkane dehydrogenation reactions.